Early Initiation of Sacubitril/Valsartan in Patients With Acute Heart Failure and Renal Dysfunction - STRABURZYNSKA-MIGAJ, E. W.A. (2023)
Funding Information: This study was funded by Novartis . Funding Information: This study was funded by Novartis. The authors thank Tripti Sahu of Novartis Healthcare Pvt. Ltd. for providing medical writing support in accordance with Good Publication Practice (GPP 2022) guidelines (https://www.ismpp.org/gpp-2022). Publisher Copyright: © 2023 The Authors